Allergic contact dermatitis: early recognition and diagnosis of important allergens. - Jacob SE; Steele T (Dermatology Nursing, 2006)
Allergic contact dermatitis (ACD) is an important disease with high quality of life and economic impact. Patch testing is the procedure by which identification of the cause of ACD can be elicited. Proper performance of the test, from taking an appropriate patient history to placing the correct allergens to evaluating and educating the patient, is of utmost importance. The purpose of this article is to highlight common allergens encountered in our environment, to increase awareness for this important disease, and to underscore the importance of this testing modality. An early index of suspicion can lead to appropriate testing, diagnosis, avoidance, and cure.